MODIFIED METHODS FOR THE ANALYSIS OF THE LIGNIN-LIKE PHENOLIC POLYMER CONTENTS OF COTTON FIBERS - W. R. Hu; L. Fan; X. L. Tian; L. X. Xie (Journal of Animal and Plant Sciences, 2015)
The lignin-like phenolic polymer contents of cotton fibers are too little to be directly measured using existing methods. In this study, the thioglycolic acid (TGA), acetyl bromide (AB) and Klason methods were modified in order to determine the lignin-like phenolic polymer contents of cotton fibers. Varying sample weight, thioglycolicacidtoHCl ratios, extraction times, and degrees of acidificationto precipitate the lignin-likephenolicpolymers were used to study their effects on the TGA method. In addition, the effects of the digestive temperature, time, volume of the digestive solution, and ratio of NaOH to hydroxylamine hydrochlorideon the elimination of background absorbance in the AB method were tested. Furthermore, the effects of the drying temperature and sample weights on the measurement of lignin-like phenolic polymer contents using the Klason method were analyzed. The modified TGA, AB, and Klason methods were established based on their corresponding parameter modifications. These modified methods could be directly used to determine the contents of lignin-like phenolicpolymers in cotton fibers in different ways.
Keywords: lignin-like phenolic polymers; cotton fiber; thioglycolic acid (TGA); acetyl bromide ( AB); Klason method